Pengaruh Penggunaan Aplikasi Canva terhadap Minat Belajar Siswa pada Materi Matriks Kelas XI SMAN 1 Cigugur - Pebriyanto, Riyan; Hermawan, Hermawan (Lembaga Intelektual Muda (LIM) Maluku, 2024)
Canva learning media is an online platform for graphic design in designing various creative designs to make it easier for users, such as designing posters, info graphics, and presentations. Not only for designing, but can also be used as a learning medium for teachers, students and schools in classroom learning. The aim of this research is to determine the effect of using the Canva application on interest in learning in class XI matrix material at SMAN 1 Cigugur. This research uses a quantitative approach with a quasi-experimental method. The research design is nonequivalent control group design. The research sample consisted of 67 students in two classes, one control class, namely class XI 5 and one experimental class, namely class the results of data analysis show that there is an influence of applying Canva learning media on interest in learning. Meanwhile, in the Independent Sample T Test, a significance result was obtained of 0.000 < 0.05, so it can be concluded that there is a significant difference between the average results of learning interest in students who use Canva learning media and conventional learning using the PDF file application